A refined ring polymer contraction scheme for systems with electrostatic interactions - Markland, T; Manolopoulos, D (2008)
We have recently shown how path integral simulations can be streamlined by decomposing the potential into a sum of rapidly-varying short-range and slowly-varying long-range contributions. Here, we introduce an efficient way to perform this decomposition for systems with electrostatic interactions and illustrate the method with an application to a flexible water model. In the limit of large system size, where the calculation of long-range forces dominates, the present method enables path integral simulations of liquid water to be performed with less than twice the computational effort of classical molecular dynamics simulations. © 2008 Elsevier B.V. All rights reserved.